La necesidad de que el Derecho Penal se (pre)ocupe de la ejecución de la pena de prisión - Alemán Aróstegui, Lorena (Eguzkilore, 2021)
Execution of imprisonment is a field that is characterized by deriving from criminal conviction. In this field, different rules, which are laid down in diverse legal texts, come together, and different agents from judicial bodies such as prison administration or prison supervision courts are involved, among others. This special configuration along with other reasons have made Criminal Law not to be as (pre)occupied with the execution of imprisonment as with other issues, especially, in relation to the enforcement of criminal principles and guarantees. This paper aims at presenting the reasons why it is possible to claim that Criminal Law should and must be (pre)occupied with the execution of imprisonment: the proposal of a comprehensive conception of the punishment that includes the moment of its execution; the considerations which, departing from punishment theories, are made of the execution phase through critical approaching of these theories; the confirmation that penal reforms implemented in recent decades have modified the execution of imprisonment model; and how fundamental rights can be affected during imprisonment as a consequence of the “relaxation” of the principle of legalty. The way that this preoccupation should follow is also addressed: the necessity to safeguard the validity of criminal guarantees during the execution of imprisonment.